Alternatively Spliced BnaPAP2.A7 Isoforms Play Opposing Roles in Anthocyanin Biosynthesis of Brassica napus L. - Chen, Daozong; Liu, Yi; Yin, Shuai; Qiu, Jie; Jin, Qingdong; King, Graham J.; Wang, Jing; Ge, Xianhong; Li, Zaiyun (Frontiers in Plant Science, 2020)
Brassica napus L. (rapeseed, oilseed rape, canola) and varieties of its two diploid parents B. oleracea and B. rapa display large variation in anthocyanin pigmentation of leaf, stem and fruit. Here, we demonstrate that BnaPAP2.A7, an ortholog of the B. oleracea anthocyanin activator BoMYB2 that confers purple traits, positively regulates anthocyanin biosynthesis in leaves of B. napus. Sequencing of BnaPAP2.A7 and transgenic analysis suggests that activation of this gene in purple rapeseed may result from a single nucleotide and/or 2bp insertion in its promoter region. BnaPAP2.A7 gives rise to three splice variants, designated BnaPAP2.A7-744, BnaPAP2.A7-910 and BnaPAP2.A7-395 according to the length of the transcripts. While BnaPAP2.A7-744 encodes a full-length R2R3-MYB, both BnaPAP2.A7-910 and BnaPAP2.A7-395 encode truncated proteins that lack both a partial R3 repeat and the complete C terminal domain, and so in vitro are unable to interact with the Arabidopsis bHLH protein AtTT8. Although expression of either BnaPAP2.A7-910 or BnaPAP2.A7-395 in green rapeseed does not result in purple leaves, both genes do modify genome-wide gene expression, with strong repression of anthocyanin related genes. We have demonstrated that BnaPAP.A7 regulates anthocyanin accumulation in leaves of B. napus and propose a potential mechanism for modulation of anthocyanin biosynthesis by alternative splicing.